(untitled) (Biological Sciences - PJSIR, 1998)
Studies have been undertaken to investigate kinetic data for producing light weight magnesium carbonate from magnesium sulphate and commercial soda ash solution. Using factorial planning, series of hatch-wise experiments were carried out in a 25 lit capacity stirred tank reactor (S.T.R.) at three concentration levels of the reactants (viz. low, medium and high) and two agitation levels (viz. 280 and 560 r.p.m.). It has been observed that initial concentration of Mgttions has pronounced effect both on the yield of the desired product and reaction kinetics. Whereas the agitation level/Reynolds number (within range of 6000 to 17000) has insignificant effect on the said parameter. The optimum concentrations of the reactants at which the concentration -time plot is linear arc: MgH ions 20 gl’ and Na2C01 270 gl-I. The data obtained has been applied to design C.S.T.R. which suggests that a single tank reactor (0.6m3) operating within the range of 30 -45 r.p.rn. would be economically feasible to produce 125 Kg h-I of light weight magnesium carbonate.